Review Artikel: Perbandingan Efektivitas dan Efek Samping Pembrolizumab Kombinasi Kemoterapi Dengan Kemoterapi Tunggal Dalam Pengobatan Non-Small Cell Lung Cancer (NSCLC) - Dzannuba, Fadya Laila; Hilmi , Indah Laily; Sudarjat , Hadi; Shadrina , Jahra Almas; Affandhy , Adhwa’a Kaylla (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
This review article aims to compare the effectiveness and side effects of pembrolizumab combined with chemotherapy versus chemotherapy alone in the treatment of advanced Non-Small Cell Lung Cancer (NSCLC). A systematic review was conducted using literature published between 2015 and 2024. Relevant studies were identified through databases such as Google Scholar, using keywords like